Efficient Energy-Conversion Materials for the Future: Understanding and Tailoring Charge-Transfer Processes in Carbon Nanostructures - Strauß, Volker; Roth, Alexandra Marina; Sekita, Michael; Guldi, Dirk Michael (Chem, 2016)
In this review, we survey the role of carbon-based nanomaterials in energy-conversion schemes. In particular, we highlight charge-transfer processes on the molecular scale in sp2 carbon in zero dimensions (fullerenes), sp2 carbon in one dimension (carbon nanotubes), sp2 carbon in two dimensions (graphene), and sp2/sp3 carbon in zero and two dimensions (defectuous carbon nanostructures). As such, we conclude that the versatility of carbon-based nanomaterials in terms of structural and electronic properties renders them broadly applicable electroactive components for future energy devices.
CRIS-Team Scopus Importer:2023-03-07
Keywords: artificial photosynthesis; carbon nanodots; carbon nanostructures; carbon nanotubes; charge transfer; fullerenes; graphene; light harvesting